2015
DOI: 10.1186/s12960-015-0064-9
|View full text |Cite
|
Sign up to set email alerts
|

Feminization of the medical workforce in low-income settings; findings from surveys in three African capital cities

Abstract: BackgroundWomen represent an increasingly growing share of the medical workforce in high-income countries, with abundant research focusing on reasons and implications of the phenomenon. Little evidence is available from low- and middle-income countries, which is odd given the possible repercussion this may have for the local supply of medical services and, ultimately, for attaining universal health coverage.MethodsDrawing from secondary analysis of primary survey data, this paper analyses the proportion and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 38 publications
2
52
0
6
Order By: Relevance
“…Appropriately, most women in our study sought formal help from a General Practitioner (GP) or a Gynecologist for their conditions. Ghana, like most countries, is undergoing a gender redistribution of the physician workforce [71][72][73][74]. The estimated 1:8,481 patient to provider ratio [75] has traditionally tipped in favor of male doctors [76][77][78][79], including Obstetric/Gynecologists (ObGyns) [80], even though there is ample literature to support the notion that women, particularly those in conservative cultures, prefer female OB-GYNs, given the intimacy of the services rendered by these providers [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…Appropriately, most women in our study sought formal help from a General Practitioner (GP) or a Gynecologist for their conditions. Ghana, like most countries, is undergoing a gender redistribution of the physician workforce [71][72][73][74]. The estimated 1:8,481 patient to provider ratio [75] has traditionally tipped in favor of male doctors [76][77][78][79], including Obstetric/Gynecologists (ObGyns) [80], even though there is ample literature to support the notion that women, particularly those in conservative cultures, prefer female OB-GYNs, given the intimacy of the services rendered by these providers [81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…The feminisation of the health workforce-the movement of women into occupations where they were formally under-represented [1]-is a phenomenon that has been extensively documented in global health research [1][2][3][4][5][6][7][8][9][10][11][12][13]. In medicine, women have moved from exclusion from the profession to the majority of medical graduates in many countries around the world [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In medicine, women have moved from exclusion from the profession to the majority of medical graduates in many countries around the world [2,3]. Feminisation of the medical profession has been recorded in countries as diverse as Bangladesh [4], Canada [5], Cape Verde [6], Guinea Bissau [6], Israel [7], Mozambique [6], Oman [8], the UK [3] and the US [9]. In dentistry, the proportion of women is projected to increase to 28% globally by 2030 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, subsequent studies have found that women physicians in Mexico are underemployed, though the reasons for this (e.g., whether this is because of discrimination in graduate training, occupational choices, or working in public vs. private sectors) are not completely understood [7]. A recent study including physicians in three African capital cities found the proportion of women physicians to range from 28.1% in Bissau, Guinea-Bissau to 56.4% in Praia, Cape Verde, and that women across all three cities were over-represented in the younger age groups [8]. Further, women physicians also predominated in primary care specialties and on average worked fewer hours per week than their male peers, particularly in the private sector.…”
Section: Introductionmentioning
confidence: 99%